Sum

Find `dy/dx,if e^x+e^y=e^(x-y)`

Advertisement Remove all ads

#### Solution

`e^x + e^y = e^(x – y)`

diff. w.r.t. x

`(de^x)/dx+(de^y)/dx=(de(x-y))/dx`

`e^x + e^y dy/dx=e^(x-y) (1-dy/dx)`

`(e^y + e^(x – y))dy/dx=e^(x-y)-e^x`

`dy/dx=((e^(x-y)-e^x)/(e^(x-y+e^y)))=(e^x+e^y-e^x)/(e^x+e^y+e^y)`

Concept: Increasing and Decreasing Functions

Is there an error in this question or solution?

Advertisement Remove all ads

#### APPEARS IN

Advertisement Remove all ads

Advertisement Remove all ads